Gold(III)/Sodium Diphenylphosphinobenzene-3-sulfonate (TPPMS) Catalyzed Dehydrative N-Benzylation of Electron-Deficient Anilines in Water - Hikawa, Hidemasa; Matsumoto, Mika; Tawara, Sayoko; Kikkawa, Shoko; Azumaya, Isao (Synthesis, 2019)
A strategy for the dehydrative N-benzylation of electron-deficient anilines in water has been developed. The gold(III)/sodium diphenylphosphinobenzene-3-sulfonate (TPPMS) catalyst is highly effective as a Lewis acid for the activation of alcohols and tolerates aerobic conditions. A Hammett study in the reaction of para-substituted benzhydryl alcohols shows negative σ values, indicating a build-up of cationic charge during the rate-determining sp3 C–O bond-cleavage step. The inverse kinetic solvent isotope effect (KSIE = 0.6) is consistent with a specific acid catalysis mechanism. This simple protocol can be performed under mild conditions in an atom-economic process without the need for base or other additives, furnishing the electron-deficient N-benzylic anilines in moderate to excellent yields along with water as a sole coproduct.
Keywords: gold; water; benzylic alcohol; aniline; N-benzylation